IMPLEMENTASI PROGRAM CINTA (CICING TENANG TANPA RUNTAH) BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) DALAM MENINGKATKAN KOMPETENSI KEBERLANJUTAN MURID SEKOLAH DASAR - Pancarini, Kus; Nurul Maulida, Vita; Mahpudin, Pupud; Mirnawati, Mira; Jaenudin, Dadang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low environmental awareness and the suboptimal implementation of Education for Sustainable Development (ESD) in primary schools pose challenges to fostering students' "competence of will" (the motivation and commitment to act). This study aims to analyze the implementation of the ESD-based CINTA Program (Cicing Tenang Tanpa Runtah) in enhancing the participatory competence of primary school students. A descriptive qualitative approach was employed at SDN BL 2, involving 27 students and 10 teachers selected through purposive sampling. Data were collected via observation, questionnaires, and documentation, and subsequently analyzed using the Miles and Huberman model comprising data reduction, data display, and conclusion drawing with source and technique triangulation to ensure data validity. The results indicate that the CINTA Program successfully integrated the three pillars of ESD environmental, social, and economic into the school culture and learning processes. Program implementation led to an increase in students' competence of will, evidenced by improvements in environmental awareness (from 35% to 85%), responsibility (from 20% to 75%), participation (from 55% to 90%), and eco-friendly behavior (from 35% to 85%). The program also contributed to the development of critical thinking, collaboration, communication, and problem-solving skills through project-based activities such as waste sorting, waste bank management, and ecobrick production. Thus, the CINTA Program has the potential to serve as an effective ESD-based school culture model for enhancing students' competence of will while supporting the realization of education oriented toward sustainable development.